Implementation of Ammonia (NH3) Gas Level Detection Tool in the Shrimp Processing Industry - Sih Harsanti, Restiani; Mustika Yasi, Ratna (Fakultas Teknik Universitas PGRI Banyuwangi, 2023)
Air contaminated with ammonia can cause respiratory problems, ammonia is colorless but has a pungent odor and is corrosive and highly toxic even at low concentrations. When ammonia enters the atmosphere and combines with air pollutants, especially nitrogen and sulfur oxide compounds from nearby vehicles, power plants and factories, it forms PM 2.5 which can be inhaled so that it can penetrate deeper into the lungs, increasing the risk of disease in the lower respiratory tract. lower. This research focuses on the implementation of an ammonia gas detector in a room that functions to detect air imbalances. This serves to overcome air pollution to employees who are in the shrimp factory production room, with this tool it can provide an early warning of excess ammonia gas in the shrimp factory production room to produce output. The ammonia gas detector in the industrial production room of the shrimp factory is based on ATMega 328P. The results showed that the average ammonia gas content in the storage room was within normal limits. The results showed that the average ammonia gas content in the storage room was within normal limits. However, the concentration of NH3 content can be increased by several other factors including the length of time of storage and the volume of shrimp in the storage room. The concentration of NH3 in the air ranges from 3-8 ppm in the shrimp storage room.